Execute Justice and Charity for Your People: Jewish Divorce Mediation as a Model for Intrareligious Peacekeeping - Nissel, Sarah M. (Religions, 2025)
This article explores the complex issue of disharmony within religious marriages, focusing on Jewish approaches to divorce. Contrasting Jewish divorce mediation with other religions’ approaches to marital conflict, this article examines two Judaic models: one viewing divorce as a severe remedy permissible only under certain circumstances, and the other allowing for divorce when a marriage is irreparably broken. The author highlights the positive Jewish commandment to peacefully divorce, discussing how mediation integrates compassion and justice, in line with Jewish legal and ethical traditions. This work emphasizes the benefits of community-based divorce mediation, including lower costs, shorter timelines, and increased communal acceptance. Jewish divorce mediation, the author argues, is particularly effective in maintaining child-centeredness and co-parenting relationships post-divorce. This article calls for a broader adoption of Jewish divorce mediation through charitable organizations to effectuate Jewish family values and provide amicable resolutions within the Jewish community.